Kajian Kompetensi Profesional Guru Matematika Berdasarkan Hasil Wawancara di Madrasah Aliyah Kota Pekanbaru - Dwi Yana Sepvina Barus; Siti Dela Yanti; Suci Rahmadani Simanjuntak; Ade Irma (Yayasan Al-Afif, 2026)
This study examines the professional competence of mathematics teachers at Madrasah Aliyah Negeri in Pekanbaru City based on structured interview data. The research aims to describe teacher competence across five dimensions: subject matter mastery, instructional method development, learning assessment, continuous professional development, and reflective practice. Using a qualitative descriptive approach, data were collected through interviews with a mathematics teacher who has completed the PPG (Teacher Professional Education) program. Findings reveal that the teacher demonstrates strong professional competence through systematic lesson preparation, differentiated instruction using tiered worksheets, scaffolding strategies, and integration of educational technologies such as GeoGebra, Quizizz, and Kahoot. Active participation in MGMP and professional seminars further supports sustainable professional growth. This study concludes that professional competence must be complemented by pedagogical, social, and personality competencies for truly effective and ethical teaching practice.